The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1123/jpah.2019-0320
|View full text |Cite
|
Sign up to set email alerts
|

Academic Achievement and Physical Activity: The Ideal Relationship to Promote a Healthier Lifestyle in Adolescents

Abstract: Background: School environment provides several intervention opportunities for physical activity. The aim of this study was to examine the relationship between objectively assessed moderate to vigorous physical activity (MVPA) and academic achievement in adolescents. Methods: Cross-sectional data were collected from 301 students aged between 13 and 15 years (46.51% boys), enrolled at 7 secondary schools in the city of Huesca (Spain). Participants wore accelerometers during a 7-day period, and their academic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Briefly, the past research is mix and inconclusive, wherein some investigations found a positive relationship between some PA intensities (vigorous or MVPA) to academic performance, [33][34][35][36] others showed that association mediated via other variables, 31,37 others found no association 30,[38][39][40][41][42] or even a negative link. 43,44 Additionally, some studies have considered the joint effect of the MVPA, 29,35,38,40,42,45 and others have distinguished between different PA intensity levels. 34,36,43,46 However, only three longitudinal studies examined this association and were unable to produce consistent conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the past research is mix and inconclusive, wherein some investigations found a positive relationship between some PA intensities (vigorous or MVPA) to academic performance, [33][34][35][36] others showed that association mediated via other variables, 31,37 others found no association 30,[38][39][40][41][42] or even a negative link. 43,44 Additionally, some studies have considered the joint effect of the MVPA, 29,35,38,40,42,45 and others have distinguished between different PA intensity levels. 34,36,43,46 However, only three longitudinal studies examined this association and were unable to produce consistent conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…In the Spanish adolescent population, results showed a significant negative relationship between PA levels during the week and AA, and no relationship with PA on the weekend. However, the male group that reached levels of PA close to compliance with the recommendations developed by the US Department of Health and Human Services (60 min of daily moderate–vigorous PA) [ 10 ] was more likely to obtain high AA [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Estrada-Tenorio et al, 2020;Owen et al, 2018). En el caso de las chicas con AACC, esto implicaría que ciertos niveles de AF se correlacionan de forma positiva con el RA total, mientras que niveles de AF demasiado bajos o demasiados altos se asocian a un menor RA.…”
unclassified